Analisis Sikap Percaya Diri Siswa Melalui Kegiatan Menarik dan Menantang Pramuka Pada Kelas II UPTD SDN Gili Timur 2 Bangkalan - A’yunun Nadhirah; Adtya Dyah Puspitasari (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2024)
The aim of this research is "Describe how trusting is students themselves through the scouting method 'Interesting and challenging activities' on Scout extracurricular node material in class II UPTD SDN Gili Timur 2 Bangkalan”. This research is a qualitative research. The type of research is field study. The population used is alert students. Samples used 1 male standby student and 1 female standby student. Data collection techniques use observation, documentation and interviews. Data validity techniques using Triangulation. The triangulation used is technical triangulation and triangulation source. Triangulation techniques for conducting observations, interviews and documentation. Triangulation of sources using student sources, scout leaders and teachers. Results From data analysis, it states that the attitude of self-confidence that emerges is self-confidence, assertiveness, responsibility and positive thinking.